Phytochemical and Pharmaceutical Importance of Ipomoea staphylina Roem. and Schult: A Medicinal Review - G, Kokila.; P, Jeevan. (Asian Journal of Biological and Life Sciences)
Plant based remedies are best alternative to allopathic medicine. They have been contributed significantly to rural livelihoods. Apart from the traditional healers used herbal medicine, many people are involved in the collection and trading of medicinal plants. This has been resulted an increasing demand for herbal remedies worldwide leading to enhance new drugs. The bioactivity of natural compounds is associated with the effects of various phytochemicals such as alkaloids, tannins, cardiac glycosides, terpenoids, saponins, flavonoids etc. In this study the medicinal plant Ipomoea staphylina was reviewed. This plant was widely used for the treatment of various diseases like cancer, diabetes, inflammation, oxidative stress, pathogenic infection etc. reported by various authors. Moreover, this plant was used by many tribal people for the treatment of many diseases included antidote. Thus the plant might be useful for discovery of new natural drugs for many diseases after detailed study.
Keywords: Bioactive compounds; Diabetes and Cancer; Ethnobotanical; Ipomoea staphylina; Phytochemistry